Effect of gender on symptomatic gallstone - Shah, Surendra; Shrestha, S; Agrawal, CS (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction: Laparoscopic cholecystectomy (LC) is generally preferred over conventional open cholecystectomy (OC)for cholelithiasis. This study was conducted to analyze the effect of gender on the severity of symptomatic gallstonedisease and difficulties in laparoscopic cholecystectomy.Method: This was a cross-sectional study from February 15, 2007 to February 14, 2008 in the department of surgeryat B P Koirala Institute of Health Sciences (BPKIHS), Dharan, Nepal. All the patients with symptomatic gallstone diseasewho were underwent cholecystectomy were included in the study. Those patients, who underwent cholecystectomy inassociation with other abdominal surgery, were excluded from the study.Result: The peak age of patients who underwent cholecystectomy for gallstone in male was 41 to 60 years and in female21 to 40 years. Acute cholecystitis was common in male i.e. 28 (39.44%). Distended gallbladder, thickened gallbladderwall, adhesion to gallbladder, and frozen calot’s triangle were common intraoperative findings in male. Duration of surgery,conversion, blood loss, and post-operative complications were similar in both gender.Conclusion: Male are a risk factor for severe symptomatic gallstone disease which causes difficult dissection but we didnot find increased morbidity or complications (intraoperative or post-operative).